Cervicalgias e lombalgias após acidente de viação. Os desafios da avaliação do dano pessoal - Miguel Dias Moreira (2021)
Introduction: Neck and low back pain are increasingly common complaints after road traffic accidents (RTA) and their causal link isn't always clear, due to the absence of objective lesions, high prevalence of degenerative spine pathology and possible search for monetary gain in cases involving insurance companies. This study aims to increase knowledge about neck and low back pain after RTA when an insurance company is involved. Methods: Starting from an anonymized database provided by an insurance company, inclusion criteria were established and two groups formed: those presenting with isolated complaints, temporary or permanent, of neck and low back pain (G1), and those that in addition to these presented with lesion (excluding spine or spinal cord). Results: For 69.6% of cases, complaints became permanent with differences between G1/G2 (p=0.019). In G1 these cause prolonged medical leave (>80 days), Quantum Doloris, Permanent Functional Deficit (61.5% of cases), additional effort for previous activity (14.1%) and Permanent Repercussions on Sports and Leisure Activities (7,3%), leading to a compensation worth pursuing. As for causal link, it wasn't established in 2.7% and only partially established in 38.5%, considering previous state. Discussion: The complaints in study can't be fully attributed to RTA in all cases due to the high prevalence of degenerative pathology and possible economical interest. Therefore, more and better evidence is fundamental, allowing for a better differential diagnosis based on a more consistently secure causal link.